Towards a Novel Family of Algorithms in Pursuit Navigation. Issue 1 (2nd January 2020) - Attarchi, Hassan; Bidabad, Behroz; Torbaghan, Seyed Mehdi Kazemi; Khosravi, Mohammad Reza
Abstract: The problem of tracking and navigation towards a moving target is always one of the main topics in robotics. In this paper, following our recent work in the plane, a novel on-line strategy is used to guide a pursuer in space. This strategy is called hybrid pursuit navigation and it is a combination of two well-known pursuit algorithms the pure-pursuit and the pure-rendezvous navigation. To show the reliability of this new method, it is proved that the pursuer reaches the target under the hybrid pursuit navigation. Moreover, by simulating different scenarios, the advantage of this algorithm is demonstrated in comparison with two well-known algorithms.